Application Of Some Teaching Methods in Mathematics Lessons in Elementary Grades - Fozilov Jakhongir Ibrokhimovich; Abduraxmonova Mohinur Furqatjon qizi (Zien Journals, 2022)
This material discusses the possibility of using some pedagogical technologies in mathematics lessons.
Keywords: mathematics; primary school; teaching methods; performance